Efecto de un complejo probiótico en el agua de bebida sobre los parámetros productivos de gallinas de postura HY- LINE BROWN en etapa de levante - Deza Espino, Lucio Gerardo (2011)
This research was carried out in the Guadalupe district, Province of Pacasmayo, La Libertad Department, with the objective of determining the effect of a probiotic complex (CP) in the productive performance of laying hens Hy Line Brown. We used a completely randomized design with 2 treatments (control and treatment) with 4 replicates and each replicate with 50 birds experimental units. Weights were evaluated weekly, feed intake, feed conversion and uniformity using the ANOV A for that purpose and for mortality was used the chi-square. The results findings indicate show that the application of improved probiotic complex pesos a week until the eighth week (21.61g ± 561.45 vs 692.13 ± 20.76 g) there were highly significant differences (p <0.01), but the eighth in the 15 weeks there were no Significant differences (p> 0.05) (44.28g ± 1265 vs 1284 ± 45.86 g). Feed intake was lower in the experimental group (38.16g ± 43.87g ± 3.21 vs 4.32), and feed efficiency did not differ significantly (p <0.05) in the treatment being of 3.21 ± 0.18 compared to control was of (3.97 ± 0.15). The percentage of uniformity was 81.56% for the experimental group were significantly different (p <0.05) compared to control (73.83%). With regard to mortality rate differences were significant (p <0.05), 3.5% and 1.3% for the control group and treatment group respectively. We conclude the application of the complex probiotic in the drinking water at 1 mg 1 day 1 bird, improved production characteristics oflaying pullets Hy-Line Brown line to the eighth week ofthe release stage.